Factors of Weight Loss for Telemedically Supported Metabolic Syndrome Patients in a Controlled Trial - Brigitta Szálka; István Vassányi; Éva Máthéné Köteles; Lili Adrienn Szabó; Szilvia Lada; Tímea Bolgár; Andrea Korom; Judit Ábrahám; Vilmos Bilicki; Mária Barnai; Attila Nemes; Csaba Lengyel; et al. (Applied Sciences)
Metabolic syndrome (MetS) is a complex of interrelated risk factors, associated with several serious chronic diseases like diabetes. The goal of this study was to find dietary factors of successful weight loss for MetS outpatients. We performed a 90-day dietary intervention in a telemedically supported, pre- and post-test, controlled trial in Hungary involving 132 MetS patients; 67 were in the intervention, and 65 were in the control group. Patients in the intervention group used wireless smart devices, a dietary logger, and a lifestyle app. During the trial, we recorded the patients’ weight loss and diet composition. For analysis, t-tests were used, and the temporal trends of diet composition in the intervention group were analyzed between two sub-groups according to weight loss success. Correlation and regression models were used to find predictors of success. The intervention group achieved more weight loss, and the success in this group was linked with more consumption of raw fruits/vegetables, poultry and potato dishes, while age had a negative effect. We conclude that telemedically supported dietary coaching is an efficient alternative for interventions directed at weight loss. Future trials should investigate the therapeutic application of diets rich in raw fruits, especially apples, and vegetables, as well as poultry dishes.